Efficient and stable TiO2/Sb2S3 planar solar cells from absorber crystallization and Se-atmosphere annealing. (March 2017) - Deng, Hui; Yuan, Shengjie; Yang, Xiaokun; Cai, Fensha; Hu, Chao; Qiao, Keke; Zhang, Jian; Tang, Jiang; Song, Haisheng; He, Zhubing
Abstract: Inorganic Sb2 S3 thin film solar cells show wide application prospects in low cost, non-toxicity and high stability solar cells comparing with well-developed CIGS, CdTe and organohalide perovskite materials. The present work successfully fabricated Sb2 S3 film utilizing rapid thermal evaporation (RTE) method. By optimizing the crystal growth technique, smooth and non-pinhole Sb2 S3 film was deposited on compact TiO2 substrate. The corresponding planar TiO2 /Sb2 S3 solar cells without hole transport material (HTM) assistance achieved an efficiency of 2.5%. To eliminate S-shape J-V curves and improve the fill factor, the as-deposited Sb2 S3 film was further annealed in selenium atmosphere. The efficiency and fill factor of Se-atmosphere annealed Sb2 S3 devices were improved to 3.2% and 55%, respectively. The device improvement mechanism of Se-annealing process were systematically illustrated by cryogenic measurements, impedance analysis and capacitance-voltage characterizations. The post-annealing could help to improve junction quality, passivate absorber defects and decrease back contact barrier. The Se-atmosphere annealed Sb2 S3 devices could stand continuous one sun illumination for 400 h and the efficiency was almost the same. After storing in air for six months, the average efficiencies still hold more than 90% of initial value. The present developed environment-friendly stable devices and efficient treatment technique were expected to enrich the research of thin film solar cell. Graphical abstract: Highlights: The present work successfully fabricated Sb2 S3 film utilizing rapid thermal evaporation (RTE) method. By Se-atmosphere annealing, the efficiency of HTM free planar Sb2 S3 devices reached 3.2%. The device improvement mechanism of Se-annealing process was systematically illustrated. The Sb2 S3 devices could keep stable after continuous 400 h illumination and 6-month storage.